SISTEM INFORMASI ABSENSI MAGANG (KERJA PRAKTIK) PADA PERUMDA TIRTA MUSI PALEMBANG - Dwi Putri Amanda; Fathiyah Nopriani (CV. Denasya Smart Publisher, 2024)
This research proposes the development of a digital-based Internship Attendance Information System. This system is designed to make it easier to manage internship participant attendance data effectively and efficiently. By using this information system, it is hoped that the entire attendance recording process can be carried out automatically, attendance data is stored safely, and attendance reports can be generated quickly and accurately. This research will use a system development method (System Development Life Cycle, SDLC) with a prototyping approach. The stages in this method include gathering requirements, building a prototype, evaluating the prototype by users, refining the prototype, and implementing the final system. The data used in this research was collected through interviews with Perumda Tirta Musi staff, field observations, and study of related documents. It is hoped that the final results of this research will produce an information system that can be implemented and help Perumda Tirta Musi in managing internship attendance better, with a focus on meeting user needs through continuous iteration and feedback.